Pengembangan Agroindustri Pengolahan Hasil Pertanian Kelompok Wanitatani di Kecamatan Kediri Kabupaten Lombok Barat - Dwi Praptomo Sudjatmiko; Muhamad Siddik; Anwar Anwar; Anas Zaini; Bambang Dipokusumo (Universitas Mataram, 2023)
The income of farm households that rely on the cultivation subsystem has so far been relatively low, so it is necessary to look for additional income such as processing agricultural products such as chilies and tomatoes which are easily damaged. Montong Are Village, Kediri District, has the potential to produce chilies and tomatoes, which when the main harvest prices fall, so it requires yield processing technology that can be obtained from training activities which are part of community service activities. The objectives of this activity are to: (1) increase the knowledge, skills and attitudes of women farming in agricultural product processing activities through training, (2) increase the quantity and quality of processed agricultural products, and (3) produce scientific publications. The target group is a member of a women's group of 30 people from 3 groups in Montong Are Village, Kediri District. The method used in community service activities is participatory based training where women farmers will be actively involved in every activity. Implementation of activities includes: outreach, Focus Group Discussion (FGD), training, and practice of processing agricultural products. The results of the training showed that there was an increase in knowledge for training with chili processing material by 50.45% and for training with tomato processing material there was an increase of 52.25%. In general, there was an increase in the volume of processed chili (sambal clove) and tomato sauce production, although it was not significant because at the time of activity, the production of chili and tomatoes was not much and the price was still high enough that it was not urgent to process them into processed chili/sambal and tomato sauce products. Later, if production is abundant and prices fall, processing of agricultural products, especially chilies and tomatoes, can be carried out.